2017
DOI: 10.1371/journal.pone.0184345
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin, thromboxane and glomerular filtration rate are abnormal in sickle cell pregnancy

Abstract: BackgroundPregnancy increases the risk of morbidity and mortality in sickle cell disease. We previously showed pregnant women with sickle cell disease to have a relatively low plasma renin concentration in late pregnancy, associated with a lack of the expected plasma volume expansion. We hypothesized this to be due to increased systemic vascular resistance through an imbalance between the vasodilator prostacyclin and vasoconstrictor thromboxane, associated with decreased glomerular filtration rate (GFR).Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These hormonal differences were associated with decreased plasma volume expansion and increased systemic vascular resistance. 20,21 This study is limited by its retrospective, observational nature, which contributes to missing data and inconsistent blood pressure measurement techniques. However, the rate of missing data in our sample is not different between compared groups and is most associated with year of pregnancy, as a function of sites' electronic medical record transitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hormonal differences were associated with decreased plasma volume expansion and increased systemic vascular resistance. 20,21 This study is limited by its retrospective, observational nature, which contributes to missing data and inconsistent blood pressure measurement techniques. However, the rate of missing data in our sample is not different between compared groups and is most associated with year of pregnancy, as a function of sites' electronic medical record transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated abnormally low prostaglandin to thromboxane ratios during pregnancy in people with HbSS compared to unaffected pregnancies. These hormonal differences were associated with decreased plasma volume expansion and increased systemic vascular resistance 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…Progressive ischemic stroke is a common cerebrovascular disease in clinical practice, with a high morbidity and extremely high rate of fatality and disability. Progressive ischemic stroke is a serious threat to the health and life of those affected, and is a prominent disabling and fatal disease (10). For patients with acute ischemic stroke, it is essential to optimize the treatment effect and reduce the rates of disability and fatality via timely diagnosis and the formulation of targeted treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…Even when these women do not die, a large proportion of them end up as 'maternal near miss', meaning they would have died but for prompt and appropriate intervention. 8 Choice of comparator Previously, we found a reversal in prostacyclin-thromboxane ratio in pregnant haemoglobin SS (HbSS) women, 9 a situation that is also found in non-sickle pregnancies with PE and unexplained IUGR. 10 Low-dose aspirin (LDA) has been shown to reduce the incidence of PE and IUGR in high-risk women due to its reduction of vasoconstrictor thromboxane while sparing prostacyclin, in effect correcting the ratio.…”
Section: Introduction Background and Rationalementioning
confidence: 95%